2014
DOI: 10.1016/j.repc.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Ablação epicárdica para prevenção da fibrilhação ventricular em doente com síndrome de Brugada

Abstract: We present the case of a 60-year-old woman with Brugada syndrome, permanent type 1 electrocardiographic pattern, who had previously received an implantable cardioverter-defibrillator. She suffered frequent syncopal episodes and multiple appropriate shocks (around five per month) due to polymorphic ventricular tachycardia/ventricular fibrillation, refractory to quinidine therapy. Combined epicardial and endocardial electroanatomical mapping was performed with a view to substrate ablation. An area of abnormal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These authors hypothesized that these areas of slow conduction represent areas of delayed depolarization due to micro-anatomic or functional derangements in conduction between cardiomyocytes, which lead to the characteristic ST-segment elevation pattern seen in BrS [7]. This study led to case reports of epicardial ablation for prevention of ventricular arrhythmias in BrS patients refusing ICD implantation [24] and recurrent VT/VF [25]. Recently, Brugada, Pappone and colleagues also reported that ablation of low-voltage areas on the epicardial surface of the anterior RVOT and anterior RV free wall was associated with non-inducibility of VT/VF in the electrophysiology lab, and normalization of the surface ECG in 14 BrS patients who had received an ICD [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors hypothesized that these areas of slow conduction represent areas of delayed depolarization due to micro-anatomic or functional derangements in conduction between cardiomyocytes, which lead to the characteristic ST-segment elevation pattern seen in BrS [7]. This study led to case reports of epicardial ablation for prevention of ventricular arrhythmias in BrS patients refusing ICD implantation [24] and recurrent VT/VF [25]. Recently, Brugada, Pappone and colleagues also reported that ablation of low-voltage areas on the epicardial surface of the anterior RVOT and anterior RV free wall was associated with non-inducibility of VT/VF in the electrophysiology lab, and normalization of the surface ECG in 14 BrS patients who had received an ICD [8].…”
Section: Discussionmentioning
confidence: 99%
“…They targeted bipolar electrograms with delayed fractionated potentials (up to 370 ms after the surface QRS complex) on the anterior RVOT wall. The surface ECG normalized six weeks after ablation, and no recurrent VT/VF episodes were observed over a 6-month follow-up [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the AS responsible for abnormalities seen in the ECG in BrS to be located in the RVOT ( Lambiase et al, 2009 ; Nademanee et al, 2011 ; Sunsaneewitayakul et al, 2012 ; Cortez-Dias et al, 2014 ; Rudic et al, 2016a ). Studies in rabbit myocytes suggest this may be partially explained by a wider range of action potential durations (APDs) in RVOT myocytes compared to RV myocytes, which is an important factor in arrhythmogenesis ( Liang et al, 2012 ).…”
Section: The Arrhythmogenic Substratementioning
confidence: 99%
“…Subsequent case reports have been published in support of these effects. 212 Ablation therapy may be life-saving in uncontrollable cases, or BrS cases in which ICD therapy is impractical (e.g. contraindications or financial hardship in developing countries).…”
Section: Approach To Therapymentioning
confidence: 99%